OFR-91-84 Development Of Roof Control Criteria For Underground Longwall Mining - S. S. Peng (The National Institute for Occupational Safety and Health (NIOSH), 1984)
Successful longwall mining requires a good roof control. A good roof control implies that: (1) no excessive pressure is build up in the face powered supports, and (2) chain pillars are designed in such a way that panel entries are well protected and interactions between adjacent panels are minimized. A clear understanding of strata behavior around longwall panels due to face movement is, therefore, the foremost requirement for achieving better roof control. This dissertation is designed to analyze the effects of strata behavior on longwall panels due to the mining activities. The following topics are studied: (1) the weighting, phenomena and their effects on front abutments, and (2) the chain pillar stability and pillar design under various roof conditions. Three dimensional finite element analysis was employed. The effect of parameters such as overburden depth, mechanical properties of the immediate roof and main roof, panel width, and size of chain pillar on (t) and (2) were analyzed. Four typical models were utilized to simulate various phases of panel extraction under various combinations of the above parameters; model one is to simulate the beginning of panel mining; model two is to simulate the situation that longwall face has passed more than half of panel length; model three is to simulate the completion of panel production; and model four is to simulate the second panel mining. The following formulae have been developed by applying multiple regression model to analyze the finite clement results: (1) a formula that classifies the type of root strata at the face area. (2) formulae that predict the first weighting and periodic weighting lengths. (3) a formula for design of the chain pillar size. Case studies were performed to check the validity of the formulae proposed. Comparison of the formulae proposed for the chain pillar design with other formulae were also performed.